REKONSTRUKSI BISNIS UMKM DI INDONESIA: REFLEKSI ATAS DAMPAK EKONOMI AKIBAT PANDEMI COVID-19 - Fajar Adhitya; Rabi’atul Adawiyah (Universitas Prof. Dr. Hazairin SH, 2021)
This study analyzes efforts in rescuing MSMEs to maintain the stability of the nationalfinancial system affected by the Covid-19 pandemic. The study uses a qualitative descriptiveapproach with data obtained from literature review and interview. The outcome of interviewconducted to 100 MSMEs in Semarang City, Demak Regency and Kendal District shows theissues faced by MSMEs due to the Covid-19 pandemic are decreased sales, difficulty inobtaining raw materials, business capitals and paying premises rents, also production anddistribution disruption. The result of the study concluded seven strategies for maintaining andincreasing MSME sales: transforming its ways of marketing and sales online, divertingproducts/services line, reallocation of funds, hygiene and halal assurance, providingvouchers or gift cards, accelerating asset sales, and reduction of labor. This research is stilllimited to one sector, that is the MSME. These seven scenarios are expected to encourageMSMEs in improving and developing its capacities so it plays the role as economic safetynets.